EVALUASI KERAGAMAN GENETIK TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI KEBUN PERCOBAAN PPKS BERDASARKAN PRIMER SSR (Simple Sequence Repeats) - Aulia, Riski (Jurnal Online Pertanian Tropik, 2017)
This research aimed to obtain information on genetic diversity populations of E. guineensis using SSR markers. This research was conducted in Biology Molecular Laboratory, Indonesian Oil Palm Research Institute, Marihat, Pematangsiantar, North Sumatera from March 2016 to November 2016. A total of 100 palm oil samples used in this research, including 20 samples from the populations of E. guineensis TR01S, including 20 samples from the populations of E. guineensis BJ022S, including 20 samples from the populations of E. guineensis BJ42S, including 20 samples from the populations of E. guineensis BO52S, and including 20 samples from the populations of E. guineensis MA19S. Calculation and Descriptive analysis in this research using software GeneMarker® version 2.40, software Power Marker V3.25, software NTSys version 2.1.1a and Microsoft Excell 2007. Research shows that the number of banding patterns detected 104 The banding patterns WITH range 8,7 per primary banding pattern and the size of the banding patterns ranging from 101 bp -328 bp. mEgCIR2569 primary is the widest primer to amplify DNA, the average of the percentage of polymorphism in the primer being used by 71% and the average value of. polymorphic information content(PIC) 0,63. At 77% genetic similarity dendogram 100 samples split into 3 groups. Lowest genetic similarity value is 75% or the highest genetic diversity was 25